Laju Pertumbuhan Bruguiera gymnorrhza dan Avicennia marina Berdasarkan Tingkat Salinitas yang Berbeda - Nadhifah, Ines; Nurweda Putra, I Dewa Nyoman (Journal of Marine Research and Technology, 2022)
Mangrove is one of the essential ecosystems on the earth and ocean. The references show that the growth rate of mangroves is affected by salinity. The study aimed to elucidate the growth rate of mangroves B. gymnorrhiza and A. marina on the different salinity concentrations. This study had been conducted for 3 months in seedbed of Balai Pengelolaan Daerah Aliran Sungai dan Hutan Lindung Unda Anyar. Five concentrations of salinity were used in this study, 0%, 0,5%, 1,5%, 2% and 3%. Several parameters of growth have been observed in this study, such as the growth of stem height, the diameter of the stem, the number of leaves, and leaf area. The parameters data were collected weekly. In this study, the data were analyzed using the One-Way Anova test. In this study, there is no significant difference (P>0.05) between growth rate and salinity, and the growth rate of B. gymnorrhiza has not been affected by salinity. However, A. marina has a significant difference (P<0.05) in one parameter, the leaf area of A. marina , and no significant difference in other parameters.